1. Life in the midst of death - Haddad, Frieda (The ecumenical review, 1983)
The main presentations on the Sixth Assembly theme and its sub-themes were accompanied by a number of brief presentations testifying to the way in which Jesus Christ is present and alive in concrete situations in different parts of the world. The following are abbreviated versions of some of those testimonies.